Extended-spectrum resistance to β-lactams/β-lactamase inhibitors (ESRI) evolved from low-level resistant Escherichia coli. (16th September 2019) - Rodríguez-Villodres, Ángel; Gil-Marqués, María Luisa; Álvarez-Marín, Rocío; Bonnin, Rémy A; Pachón-Ibáñez, María Eugenia; Aguilar-Guisado, Manuela; Naas, Thierry; Aznar, Javier; Pachón, Jerónimo; Lepe, José Antonio; Smani, Younes
Abstract: Objectives: Escherichia coli is characterized by three resistance patterns to β-lactams/β-lactamase inhibitors (BLs/BLIs): (i) resistance to ampicillin/sulbactam and susceptibility to amoxicillin/clavulanic acid and piperacillin/tazobactam (RSS); (ii) resistance to ampicillin/sulbactam and amoxicillin/clavulanic acid, and susceptibility to piperacillin/tazobactam (RRS); and (iii) resistance to ampicillin/sulbactam, amoxicillin/clavulanic acid and piperacillin/tazobactam (RRR). These resistance patterns are acquired consecutively, indicating a potential risk of developing resistance to piperacillin/tazobactam, but the precise mechanism of this process is not completely understood. Methods: Clinical isolates incrementally pressured by piperacillin/tazobactam selection in vitro and in vivo were used. We determined the MIC of piperacillin/tazobactam in the presence and absence of piperacillin/tazobactam pressure. We deciphered the role of the bla TEM genes in the new concept of extended-spectrum resistance to BLs/BLIs (ESRI) using genomic analysis. The activity of β-lactamase was quantified in these isolates. Results: We show that piperacillin/tazobactam resistance is induced in E. coli carrying bla TEM genes. This resistance is due to the increase in copy numbers and transcription levels of the bla TEM gene, thus increasing β-lactamase activity and consequently increasing piperacillin/tazobactam MICs. Genome sequencing of two bla TEM -carrying representative isolates showed that piperacillin/tazobactam treatment produced two types of duplications of bla TEM (8 and 60 copies, respectively). In the clinical setting, piperacillin/tazobactam treatment of patients infected by E. coli carrying bla TEM is associated with a risk of therapeutic failure. Conclusions: This study describes for the first time the ESRI in E. coli . This new concept is very important in the understanding of the mechanism involved in the acquisition of resistance to BLs/BLIs.